Changes in Future Synoptic Circulation Patterns: Consequences for Extreme Event Attribution. Issue 15 (5th August 2020) - Faranda, Davide; Vrac, Mathieu; Yiou, Pascal; Jézéquel, Aglaé; Thao, Soulivanh
Abstract: Anthropogenic emissions can modify the frequency and intensity of extreme weather events such as cold spells, heatwaves, and heavy precipitations. A major challenge is to detect changes in the atmospheric circulation patterns associated with those extreme events. The emergence of patterns depends on the chaotic behavior of the atmospheric flow and can also be modified by anthropogenic emissions. By embedding the circulation patterns observed during selected extremes into historical climate simulations and projections based on emission scenarios, we find major changes in probability, predictability, and persistence of atmospheric patterns observed during extreme events using an analog‐based method. The results highlight the need to take into account the role of atmospheric circulation in attribution studies as future extremes will be associated with modified circulation patterns. Plain Language Summary: Weather extreme events greatly impact agricultural, social, and economic activities. In a changing climate, it seems primordial to ask how anthropogenic emissions impact the frequency and intensity of extreme events. Attribution studies focus on this issue, often assuming that the atmospheric circulation associated with extreme events is not itself affected by climate change. We show how temporal properties of the synoptic patterns associated to extremes are affected by climate change. We explain how such changes must be taken into account in future research to perform meaningful attribution studies. Key Points: We find major changes in probability, predictability, and persistence of circulation patterns associated to extreme events Our methodology is based on embedding the circulation patterns observed during extremes into historical and future climate simulations These results warn that atmospheric circulation changes must be taken into account in future